Evaluation of electrical resistivity, residual stress and surface roughness of sputtering indium tin oxide films with different thicknesses - Tien, Chuen-Lin; Lin, Tsai-Wei; Su, Shu-Hui (Oficyna Wydawnicza Politechniki Wrocławskiej, 2021)
This paper investigates the influence of film thickness on the electrical and mechanical properties of transparent indium tin oxide (ITO) thin films. Two groups of ITO thin films deposited on unheated substrates were prepared by the radio-frequency magnetron sputtering technique. The biaxial residual stress and surface roughness for two groups of ITO thin films were measured by a Twyman–Green interferometer and a Linnik microscopic interferometer, respectively. The electrical resistivity of the ITO films was measured by a four-point probe apparatus, the thickness was determined mechanically with a profilometer. The measurement results show that the average resistivity of ITO thin films decreases with increasing the deposited thickness. The compressive residual stress in the ITO thin films decreases with increasing the deposited thickness. We also find that an anisotropic stress in the two groups of ITO films is more compressive in a certain direction. The RMS surface roughness in the two groups of ITO films is less than 1 nm.
Optica Applicata, Vol. 51, 2021, nr 4, s. 499-512
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; indium tin oxide; magnetron sputtering; residual stress; surface roughness